Brand Ambassadors and Price Drive Consumer Decisions in Indonesia - Habibil Muttaqien; Misti Hariasih (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the impact of brand ambassadors, product design, and price on purchasing decisions for Le Minerale in Sidoarjo, East Java. Using a quantitative survey method, data were collected from 100 respondents and analyzed with multiple linear regression via SPSS 25. Results show that brand ambassadors and price significantly influence purchasing decisions, while product design does not. Consumers tend to follow brand ambassadors' recommendations and are attracted to affordable pricing. These findings suggest that Le Minerale should focus on effective brand ambassador campaigns and competitive pricing to boost sales, while maintaining current product design standards. Highlights: Brand Ambassadors: Significantly influence purchasing decisions, enhancing consumer trust. Price: Positively affects purchasing decisions due to affordability. Product Design: Does not significantly impact purchasing decisions. Keywords: Brand Ambassadors, Product Design, Price, Purchasing Decisions, Le Minerale